A Bridge to the Future - Learning from the Past through Evaluation : IEG Annual Report 2021 - Independent Evaluation Group (World Bank, Washington, DC, 2021)
Much as for the rest of the World Bank Group, the past year has required an unprecedented degree of adaptation and agility from all staff at the Independent Evaluation Group (IEG). For many, fiscal year (FY)21 may feel like a bridge between the old life and the new. At the beginning of FY21, we were just growing accustomed to the full-time remote work required by a worsening global coronavirus (COVID-19) pandemic and realizing that the changes were semipermanent. At IEG, we settled in for the long haul, quickly adjusting our ways of sharing information and methods of evaluation to overcome these new challenges. By the end of the fiscal year, we had built confidence in our abilities to collect data, interview distant stakeholders, and devise new remote mission strategies. Evaluation too acts like a bridge, connecting hindsight and foresight through the objective analysis of past programs to find evidence that supports and informs positive change. Our job as evaluators is to share the insights and lessons derived from this evidence. In FY21, IEG focused on responding agilely to changing circumstances and innovating how we collected data and delivered our findings to those who needed them, when they needed them. We adapted our work program to align with the Bank Group’s COVID-19 pandemic response while continuing to build a pipeline of relevant, timely, and robust evaluations focused on long-term development challenges.